Library Automation: A Feasibility Study - Vaishnav, A.A.; Bapat, N.G. (DESIDOC Journal of Library & Information Technology, 2002)
This study deals with library automation programme of BAMUL, Aurangabad. It identifies the problems in the existing system and gives reasons for automation. The study points out the requirement of library automation and discusses the technical, social and economic aspects of library automation in detail. http://dx.doi.org/10.14429/dbit.15.2.3178